Revisiting the playbook: coaches` opinions and current views of performance, development and load monitoring in highly-trained male youth basketball players - Lever, J.; Murray, A.; Bartlett, J.; Aurellado, I.; Duffield, R.; Fullagar, H. (International Journal of Sports Science & Coaching, 2025)
This study examines basketball coaches` perceptions and current views on performance, player development, and training load monitoring in highly trained male youth academy basketball players. Through semi-structured interviews with nine coaches, we explore their philosophies on player performance, key indicators of success, and the integration of training load monitoring into their coaching practices. Reflexive thematic analysis identified 37 lower-order themes and 14 higher-order themes, which were categorized into four dimensions: Holistic Preparation, Physical and Athletic Performance, Measurement of Physical Output, and Integration of Data. Coaches emphasized psychological, skill-based, and physical aspects of player development, particularly lateral quickness, explosive movements, and coachability. While some coaches value data-informed approaches to optimize training and mitigate injury risk, others remain skeptical about its practical impact. By investigating how coaches perceive and apply performance monitoring, this study provides insights into bridging subjective coaching expertise with objective data analysis. The findings offer practical applications for sport scientists and coaching staff seeking to enhance developmental pathways for highly trained youth basketball players.